2020
DOI: 10.1016/j.ejca.2020.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing anticancer drugs for the management of COVID-19

Abstract: Since its outbreak in the last December, coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 has rapidly spread worldwide at a pandemic proportion, thus regarded as a global public health emergency. The existing therapeutic options for COVID-19 beyond the intensive supportive care are limited, with an undefined or modest efficacy reported so far. Drug repurposing represents an enthusiastic mechanism to use approved drugs outside the scope of their original indication and accelerate the discovery of new th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 226 publications
(320 reference statements)
0
60
0
Order By: Relevance
“…The peptide market has been strengthened over many years and this trend is expected to continue. During the preparation of this manuscript, it was disclosed that Plitidepsin TM (aplidin), a peptide of marine origin approved a few years ago in Australia for multiple myeloma [ 54 ], shows potent preclinical efficacy against SARS-CoV-2 [ 55 ] and is expected to enter clinical phase III very shortly. Futhermore, on 22 January 2021, voclosporin (Lupkynis TM ) was approved for the treatment of treat lupus nephritis [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peptide market has been strengthened over many years and this trend is expected to continue. During the preparation of this manuscript, it was disclosed that Plitidepsin TM (aplidin), a peptide of marine origin approved a few years ago in Australia for multiple myeloma [ 54 ], shows potent preclinical efficacy against SARS-CoV-2 [ 55 ] and is expected to enter clinical phase III very shortly. Futhermore, on 22 January 2021, voclosporin (Lupkynis TM ) was approved for the treatment of treat lupus nephritis [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drug repurposing is the use of approved drugs in an off-label use, which may reduce the cost of drug development and identify potential targetable pathways. Moreover, El Bairi et al ( 27 ) highlighted 20 anticancer drugs that have the potential and are currently being tested such as Janus kinase (JAK) pathways, monoclonal antibodies that targets vascular endothelial growth factor (VEGF), antiprotease that targets multiple receptors, inhibition of viral cellular transcription with antibiotics that have anticancer activity, immune check point inhibitors (antiprogrammed cell death), and kinase inhibitors to inhibit the cell cycle and viral life cycle. Whether a single drug or combined treatment may exhibit synergistic action against COVID-19 remains unknown and is an active area of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to a possible increased risk of herpes zoster and simplex infections, a group of Italian researchers suggested that the use of baricitinib should be considered with extreme caution (Favalli et al, 2020). Ruxolitinib is a Janus kinase (JAK) 1 and JAK2 inhibitor authorized for the treatment of myeloproliferative malignancies (El Bairi et al, 2020). The effects of the drug were evaluated in the RUXCOVID study, a phase III, multicentre, randomised and placebo-controlled trial, but its results are still not available.…”
Section: Clinical Evidence Of Immunomodulatory and Anti-inflammatory mentioning
confidence: 99%